Optimism an enduring resource for romantic relationships . [article]. - Assad, Kimberly K.
This study extends research on the adaptive aspects of dispositional optimism to romantic relationships. We hypothesized that optimism would be positively linked to cooperative problem solving in romantic relationships, given previous research indicating that optimists are likely to used approach coping strategies. Results indicated that optimism was linked to satisfying and happy romantic relationships, and a substantial portion of this association was mediated by reports of cooperative problem solving. Moreover, optimism predicted relative increases in relationship satisfaction over a 2-year interval. All told, these results suggest that optimism may serve as an enduring resource for romantic unions.
Keywords: Romantic relationships; Personality; Relationship satisfaction; Dyadic data analyses; Optimsim